A prospective observational study of community-acquired bacterial bloodstream infections in Metro Manila, the Philippines - Saito, N; Solante, RM; Guzman, FD; Telan, EO; Umipig, DV; Calayo, JP; Frayco, CH; Lazaro, JC; Ribo, MR; Dimapilis, AQ; Dimapilis, VO; Villanueva, AM; et al. (Public Library of Science, 2022)
Community-acquired bacterial bloodstream infections are caused by diverse pathogens with changing antimicrobial-resistance patterns. In low-middle income countries in Southeast Asia, where dengue fever is endemic and a leading cause of fever, limited information is available about bacterial bloodstream infections due to challenges of implementing a blood culture service. This study describes bacterial bloodstream pathogens and antimicrobial-resistance patterns in Metro Manila, the Philippines. We aimed to identify the proportion of patients with a positive blood culture, the bacteria isolated and their antimicrobial resistance patterns, and the clinical characteristics of these patients, in this dengue endemic area. We conducted a prospective observational study in a single hospital enrolling febrile patients clinically suspected of having a community-acquired bacterial bloodstream infection between 1st July 2015 and 30th June 2019. Each patient had a blood culture and additional diagnostic tests according to their clinical presentation. We enrolled 1315 patients and a significant positive blood culture was found in 77 (5.9%) including Staphylococcus aureus (n = 20), Salmonella enterica Typhi (n = 18), Escherichia coli (n = 16), Streptococcus pneumoniae (n = 3) and Burkholderia pseudomallei (n = 2). Thirty-four patients had meningococcal disease diagnosed by culture (n = 8) or blood PCR (n = 26). Additional confirmed diagnoses included leptospirosis (n = 177), dengue virus infection (n = 159) and respiratory diphtheria (n = 50). There were 79 (6.0%, 95%CI 4.8%-7.4%) patients who died within 28 days of enrollment. Patients with a positive blood culture were significantly more likely to die than patients with negative culture (15.2% vs 4.4%, P<0.01). Among S. aureus isolates, 11/20 (55%) were methicillin-resistant (MRSA) and ST30: USA1100 was dominant sequence type (88.9%). Antimicrobial-susceptibility was well preserved in S. enterica Typhi. Among hospitalized patients with clinically suspected community-acquired bacterial bloodstream infection in Metro Manila, the Philippines, 5.9% had a blood culture confirmed infection of whom 15.6% died. S. aureus, including a significant number of MRSA (USA1100 clones), S. enterica Typhi, E.coli and Neisseria meningitidis were frequently identified pathogens.